2022
DOI: 10.1177/17588359221086827
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy in metastatic hormone-sensitive prostate cancer: is three a crowd?

Abstract: The mainstay of treatment for metastatic prostate cancer is androgen deprivation therapy (ADT). Outcomes with ADT are variable but control of hormone-sensitive prostate cancer (HSPC) can often be achieved for many years. Death from prostate cancer is usually due to the development of escape variants able to survive and proliferate in the setting of castrate levels of serum androgens (metastatic castration-resistant prostate cancer, mCRPC). Several agents can improve survival for patients with mCRPC, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…As summarized in Table 1 , the management of mCSPC has undergone a paradigm shift in the past decade. Several life-prolonging therapies that have been previously used in the mCRPC setting are now showing prolonged OS benefits when used in the earlier mCSPC setting [ 9 ]. In mCSPC, docetaxel was the first systemic therapy to show an improvement in OS when added to ADT.…”
Section: Evolution Of Systemic Therapy Of Mcspc Prior To Triplet Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized in Table 1 , the management of mCSPC has undergone a paradigm shift in the past decade. Several life-prolonging therapies that have been previously used in the mCRPC setting are now showing prolonged OS benefits when used in the earlier mCSPC setting [ 9 ]. In mCSPC, docetaxel was the first systemic therapy to show an improvement in OS when added to ADT.…”
Section: Evolution Of Systemic Therapy Of Mcspc Prior To Triplet Therapymentioning
confidence: 99%
“…This is likely due to several reasons. mCSPC likely has more favorable disease biology, less acquired treatment resistance, and therefore demonstrates more durable treatment responses [ 9 ]. For example, long-term follow-up of the CHAARTED trial showed a sustained OS benefit with docetaxel (particularly for those with high-volume disease with 8-year OS of 28.5 vs. 15.4%) and a visible tail on the curve suggesting a long-term response in a subset of patients [ 29 ].…”
Section: Triplet Therapy In Mcspc—rationale and Summary Of Clinical Datamentioning
confidence: 99%
“…Only a few patients have been treated using a sequential approach in all the trials and it is still unclear whether sequencing is better than concurrent treatment [26]. Also, concomitant administration of enzalutamideþD is not recommended because of potential drug interactions and added toxicity, as seen in ENZAMET [7], but the use of triplet therapy sequentially in all patients or in risk-adapted settings based on early responses to ADTþD has not been properly investigated in any studies [5,21 & ]. Secondly, because of the small number of patients with metachronous high-volume nodal disease involved in these trials, it is presently uncertain if this cohort can also benefit from triple therapy.…”
Section: Ongoing Trialsmentioning
confidence: 99%
“…Interestingly, the evidence of ARSI is increasingly regarding as effective and safe for mHSPC 4,11 . Abiraterone acetate, the first generation of ARSIs, is a potently selective inhibitor cytochrome P-450 c17 (CYP17), constituting the most important key enzyme for testicular and extragonadal androgen biosynthesis [12][13] . Likewise, the second generation ARSI (enzalutamide, apalutamide and darolutamide) is a potent androgen receptor (AR) inhibitor 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Abiraterone acetate, the first generation of ARSIs, is a potently selective inhibitor cytochrome P-450 c17 (CYP17), constituting the most important key enzyme for testicular and extragonadal androgen biosynthesis [12][13] . Likewise, the second generation ARSI (enzalutamide, apalutamide and darolutamide) is a potent androgen receptor (AR) inhibitor 13 . The mechanism of actions includes competitive binding to AR, inhibiting androgen receptor nuclear translocation and androgen-receptors-mediated DNA binding 14 .…”
Section: Introductionmentioning
confidence: 99%